Feminilidades negras: um estudo de relações espaciais paradoxais - Silveira, Louise da (2020)
The work leaves the following question: “As the negritude while constituent element of the interseccionalidades of different femininities produces space relations paradoxical” . A rupture is lived today of what it would be the construction of the identity of the black woman and its search for emancipation, either intellectual, financial it affectively and mainly politics. The present work will present quarrels on feminism and black feminism, making one the passage of the history of the feminine black identity in Brazil and the world, clarifying the concept of race to understand as conditions of interseccionalities produces paradoxical space relations for different feminilidades therefore has a so recent past of slavery intervening, still in the present time in the space production of these black women. The space relations in the perspective of a sort geography, wrapped for a daily one that hour surprises and hour suffocates, having as approach the intersecctionality question, standing out the idea that the identity of the black woman is multiple and reaches varied oppression levels, beyond the racial one, of sort, social, amongst others. In this manner, the present work is not a mere predestinate dissertação the academy, but yes, it searchs to involve my proper black identity that wants to understand the reasons of exclusion, alienation and discrimination of the black woman, evaluating of that way these people (we), when take conscience of its situation affective politics and in the society, the spaces of being able and the militancy, finish being `pushed' for production of spaces where they have voice and time, inside of a patriarcal, racist and different system.